Pengembangan Aplikasi Pencarian Wisata Kuliner Kota Bogor Berbasis Range Harga Dan Metode Lbs (Location Base Service) Pada Android - Kusumah, Fitrah Satrya Fajar; Al Ikhsan, Safaruddin; Ahmad, Masrur (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
People interested in culinary are increase in line with application development on smartphone. Recently, developers has developed new application to find culinary places based on prices quickly and easily. This study aims to develop smartphone application to find culinary places with suitable budget for consumers. Application development method used in waterfall that consists of planning, analysis, implementation, and testing. The conclusion of this study is that the application can help consumers to find culinary places with suitable budget